2012
DOI: 10.1002/cphc.201200262
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Anchored MOF‐Based Photonic Antennae

Abstract: The loading of a metal-organic framework (MOF), [Cu(3)(btc)(2)xH(2)O] HKUST-1, with europium β-diketonate complexes is studied with the goal to using the porous molecular framework as a photonic antenna. Whereas loading of HKUST-1 powder particles produced via the conventional solvothermal synthesis method was strongly hindered, for HKUST-1 SURMOFs, thin MOF films fabricated using the liquid phase epitaxy method, a high filling factor can be achieved. The optical properties of the HKUST-1-MOFs before and after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 21 publications
1
49
0
1
Order By: Relevance
“…16,17 For both MOFs, the immobilization of the organic linkers by its incorporation into the network leads to an increase in the internal as well as external quantum yields, improving their photoluminescence properties, like luminescent and moisture stability and color tunability. 22 Others excited MOFs show ET to laser dyes (4-(dicyanomethylene)-2methyl-6-(4-dimethylaminostyryl)-4H-pyran (DCM) and Rhodamine B (Rho B)), leading to a dual emission, which was used to detect volatile organic compounds (VOCs). 18,19 The formed host-guests composites materials can exhibit different photoevents processes as charge-and energy-transfer (CT, ET).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 For both MOFs, the immobilization of the organic linkers by its incorporation into the network leads to an increase in the internal as well as external quantum yields, improving their photoluminescence properties, like luminescent and moisture stability and color tunability. 22 Others excited MOFs show ET to laser dyes (4-(dicyanomethylene)-2methyl-6-(4-dimethylaminostyryl)-4H-pyran (DCM) and Rhodamine B (Rho B)), leading to a dual emission, which was used to detect volatile organic compounds (VOCs). 18,19 The formed host-guests composites materials can exhibit different photoevents processes as charge-and energy-transfer (CT, ET).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although the time needed to grow this MOF thin film was found to be much more faster than the conventional LPE-method, the high degree of film orientation is still comparable to previously reported results. 20 Therefore, the spin coating method has many advantages over the conventional dipping LPE method, i.e. shorter preparation time, greatly reduced amount of consumed chemicals (precursors solution and solvents), and the possibility to easily coat larger surfaces up to 3x3 cm ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For further details, refer to the supplementary material. 20 The variable pressure-continuous permeate composition analysis technique was used to test the permeation of the gas mixture for the fabricated membrane. The permeate gas composition was monitored continuously until steady-state was achieved, as indicated when no change in the Mass spectrometer (MS) signal is observed.…”
Section: Methodsmentioning
confidence: 99%
“…[124] Recently, it has also been demonstrated that such deposited MOF films, also referred to as SURMOFs, can be loaded with dye molecules, thus yielding very uniform thin luminescent films. [125] Porous materials thus offer the potential to be used as microcontainers, and applications which has also been demonstrated for another highly porous material, zeolites. [126] For zeolites, however, only few studies have reported on a successful direct deposition on surfaces, but the deposition of monolayers of zeolite-platelets on appropriately functionalized substrates by m-contact printing has been demonstrated.…”
Section: Functionalization Of Surfaces By Deposition Of Porous Thin Fmentioning
confidence: 98%